GEOTHERMAL ENERGY OF THE REPUBLIC OF SRPSKA AND HYDROCHEMICAL ASPECTS OF ITS EXPLORATION AND EXPLOITATION - Andrijana Stevanović; Boban Jolović (Journal of Engineering & Processing Management, 2015)
One of the most used renewable energy sources worldwide is geothermal energy. Itrepresents the heat, originated by natural processes happen in the Earth interior. The hot springsphenomena are the most frequent natural manifestation of geothermal activity.Geothermal potentiality of some area can be estimated based on geothermal gradient. Geothermalgradient is a conductive terrestrial parameter that represents the degree of increasing of the Earthtemperature vs. depth. It is usually expressed in ⁰C/m or ⁰C/km. Different areas have differentthermal gradients and thus different geothermal potential. Generally, higher geothermal gradientscorrespond to areas containing more geothermal energy.Geothermal characteristics of the territory of the Republic of Srpska are closely related to itscomplex geological setting. It is the reason why geothermal characteristics are different from areato area. Higher geothermal potentiality is recognised in the northern parts of the entity, in the firstorder in Semberija, Posavina and Banja Luka regions.The use of geothermal energy with different fluid temperatures can be considered throughthe Lindaldiagram, who firstly proposed acomprehensive scale with appropriate temperatures for differentuses. High temperature fluids are mostly used for electricity production and moderate and lowtemperature fluids for the direct use.Despite the fact that the territory of the Republic of Srpska hasfavourable geothermal properties, utilization of this kind of renewable energy resource isinadequate. Especially indicative are data about the use of geothermal energy by heat pumps (inbad sense) in comparison with praxis of developed countries.Chemical composition of thermal waters plays very important role and can be used in itsexploration stage, for analyses of possibility of its use and for prediction of exploitation effects, aswell. This kind of renewable energyresource, highly ecologically recommended, must be consideredmore seriously in the future in the Republic of Srpska. Furthermore, it must be put into the energystrategic documentsin appropriate manner.
Keywords: geothermal; energy; sources; application